Digitalisation as a tool for economic security of a modern organisation - V. M. Svistunov; O. A. Ageeva; I. D. Matskulyak (Вестник университета, 2025)
The article examines the role of digital technologies and IT (information technologies) tools in ensuring economic security of a modern organisation. We analyse the impact of globalisation and increased competition on the need to implement   modern digital solutions for managing economic activities and assessing the legality of business processes. The authors substantiate the importance of digitalisation for improving the speed, accuracy, and reliability of the economic security system   as well as for countering external threats and realising corporate interests. The significance of an integrated approach to the implementation of the digital technologies and creation of a unified digital economic security system for the organisation is emphasised. Based on a survey of experts from various industrial enterprises, the most promising digital tools and technologies for its insurance in the next five years are identified. The problematic area of the article is digital technologies and IT tools used to improve the level of economic security of an organisation in the context of digital transformation. The purpose of the study is to identify the existing approaches to the practical use of them as an important element of the internal control system that ensures the economic security of a business entity. The main results of the can be applied in practice when solving case studies and management tasks at the level of company leaders, government institutions, and can also be included in the programme when studying the course “Economic security”.